Dynamic Mechanical and Charlesby-Pinner Analyses of Radiation Cross-Linked Ethylene-Vinyl Acetate Copolymer (EVA) - Anna Svarcova; Petr Svoboda (Molecules)
The properties of EVA copolymers with various vinyl acetate (VA) contents were compared, with EVA 206 (6 wt.% VA) and EVA 212 (12 wt.% VA) having the same melt flow indices of 2 g/10 min. The impact of electron irradiation at levels of 60, 120, and 180 kGy was studied. Four testing methods were employed as follows: wide-angle X-ray diffraction (WAXD); differential scanning calorimetry (DSC); dynamic mechanical analysis (DMA), using a high-temperature frequency sweep at 150 °C; and gel content analysis. The amount of crystalline phase was determined by WAXD and DSC. Copolymers with a higher VA content (EVA 212) had lower crystallinity. The increase in the amorphous phase allows for the greater movement of radicals, enabling them to react and form cross-links. The effects of the VA content, radiation dose, and frequency on dynamic mechanical properties were investigated by DMA. The DMA analysis focused on the shear storage modulus <semantics>G′</semantics>, damping factor <semantics>tanδ</semantics>, and complex viscosity <semantics>η*</semantics>. After irradiation, the damping factor <semantics>tanδ</semantics> decreased with an increasing VA content, indicating improved elasticity and a higher degree of cross-linking. A gel content analysis was used to calculate the parameters of the Charlesby-Pinner and Charlesby–Rosiak equations, which help with the determination of the relationship between cross-linking and chain scission. The ratio of cross-linking to scission <semantics>G(X)/G(S)</semantics> was higher for the EVA with a higher VA content (EVA 212). Due to a higher VA content (12 wt.%), EVA 212 exhibits more efficient network formation.